Wastewater surveillance of SARS-CoV-2 and influenza in a dynamic university community: understanding how wastewater measurements correspond to reported cases - Matthew J. Jones; Rukayya Ibrahim; Shirley Clark; Yolanda M. Brooks; Heather E. Preisendanz; Thomas L. Richard; Andrew F. Read; Courtney J. Robinson; Samina Noorali; Michael J. Shreve; Nina L. Dennington; Justin D. Silverman; et al. (Science of The Total Environment, 2025)

Exploring multistability in marine ecosystems: Insights from food web model dynamics - A.S. Frank; Andrea Pinke; Elizabeth Read; Susanna Röblitz; Susmita Sadhu; Sam Subbey (Ecological Modelling, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Universal School Meals During the Pandemic: A Mixed Methods Analysis of Parent Perceptions From California and Maine - Leah Elizabeth Chapman; Wendi Gosliner; Deborah A. Olarte; Lorrene D. Ritchie; Marlene B. Schwartz; Michele Polacsek; Christina E. Hecht; Kenneth Hecht; Lindsey Turner; Anisha I. Patel; Monica Daniela Zuercher; Margaret Read; et al. (Journal of the Academy of Nutrition and Dietetics, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Plant silicon application alters leaf alkaloid concentrations and impacts parasitoids more adversely than their aphid hosts - Casey R. Hall; Rhiannon C. Rowe; Meena Mikhael; Elizabeth Read; Sue E. Hartley; Scott N. Johnson (Oecologia, 2021)

First report of maize yellow mosaic virus (MaYMV) on maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherstone; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingston Mashingaidze; Dave Kenneth Berger; Tanya Welgemoed; Gerhard Pietersen; Susanna Elizabeth Schulze; Barnabas Kiula; et al. (Journal of Plant Pathology, 2019)

Objectives for management of socio-ecological systems in the Great Barrier Reef region, Australia - Ingrid Elizabeth Van Putten; Catherine Mary Dichmont; Leo Ximenes Cabral Dutra; Olivier Thébaud; Roy Aijun Deng; Eddie Jebreen; Randall Owens; Ricardo Pascual; Mark Read; Carolyn Thompson (Regional Environmental Change, 2016)

Nitrogen-fixing cyanobacteria (free-living and diatom endosymbionts): their use in southern California stream bioassessment - Rosalina Stancheva; Robert G. Sheath; Betsy A. Read; Kimberly D. McArthur; Chrystal Schroepfer; J. Patrick Kociolek; A. Elizabeth Fetscher (Hydrobiologia, 2013)

Using molecular pedigree reconstruction to evaluate the long-term survival of outplanted hatchery-reared larval and juvenile northern abalone (Haliotis kamtschatkana) - Kaitlyn D. Read; Matthew A. Lemay; Stephanie Acheson; Elizabeth G. Boulding (Conservation Genetics, 2012)

Photon echo studies of photosynthetic light harvesting - Elizabeth L. Read; Hohjai Lee; Graham R. Fleming (Photosynthesis Research, 2009)